Impact of information and communication technology (ICT) on new service development - Salvation, Mark Dirikorigha (Universiti Malaysia Pahang, 2018)
While developed countries have long begun using ICT for service innovation, many sub-Saharan African nations are still lagging behind in the use of ICTs for new service development (NSD) because of knowledge gap caused by lack of studies conducted in this area in the continent. Thus, this study attempts to close this knowledge gap by evaluating the impact of ICT on NSD in order to help service providers maximize the full potentials of ICT, including the service innovation potential. Using a survey method, a sample of 379 service-based small and medium enterprises are selected randomly from the Nigerian service industry. The data are analyzed using the Statistical Package for Social Sciences. This study is designed based on the underlying theory of Davis’ technology acceptance model (TAM) which is significant to this study. This study used the TAM theory as a basis to enhance its predictive power and the outcome of the study. The expected results show that ICT plays multiple roles in NSD. Thus, service firms are likely to use ICT for service innovation, especially if it is perceived to be useful, easy to use and with a supportive organizational culture. The study helps managers to effectively coordinate their ICT infusion into NSD to improve firm performance.